OPTIMUM ROTATION FOR EUCALYPTUS CAMALDULENSIS DEHNH. IN NORTHEAST THAILAND - Pohjonen, V.; Pukkala, T. (วารสารวนศาสตร์ไทย, 2022)
Based on dominant height/age relationship of Eucalyptus camaldulensis Dehnh, in Northeast Thailand, and on earlier stand models of eucalypts in Ethiopia, provisional yield tables for Northeast Thailand were prepared. Dominant height growth in Thai lowlands is fast for the first 10 years and notably slower thereafter. For the maximum mean annual volume increment the optimum rotation is about 10 years for fully stocked plantations and about 12 years for the commonly used spacing of 3 x 3 and 2 x 4 meters. Continuing the rotation from 5 to 10-12 years may increase the annual timber supply from the plantations by 30-50%. Denser village woodlots (2 x 2 m spacing) may be harvested about two years earlier than the industrial (3 x 3 or 2 x 4 m) plantations, for the same volume production.